2016
DOI: 10.12693/aphyspola.129.1147
|View full text |Cite
|
Sign up to set email alerts
|

Optical and Structural Properties of Cu Doped ZnS Nanocrystals: Effect of Temperature and Concentration of Capping Agent

Abstract: We have provided the Cu doped zinc sulfide (ZnS:Cu) nanoparticles using a wet chemical synthesis. In principle, the nanoparticles are provided by mixing the reactants in a double distilled water solvent. We have used the mercaptopropionic acid as the capping agent. We have obtained the physical properties of the nanoparticles using the methods: UV absorption, photoluminescence spectroscopy, and X-ray diffraction analysis. The average size of nanoparticles is obtained in the range 3-6 nm. In addition, the X-ray… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 38 publications
(33 reference statements)
0
5
0
Order By: Relevance
“…So far, the nature of the green PL band there still exists two different perspectives. These PL band can be characteristic displacement of Cu + ions (3d 10 ) 11,12) or characteristic displacement of Cu 2+ ions (3d 9 ), in which the electrons transfer from the donor V S or the interstitial atoms to the t 2 level of the Cu 2+ ions (3d 9 ) 13,15) in ZnS:Cu nanoparticles. However, in solution, the Cu + ions always tend to convert 35) to Cu 2+ and Cu, in addition, the participation of Cu + or Cu 2+ in ZnS: Cu is highly dependent on the synthesization process and the initial Cu ion source.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, the nature of the green PL band there still exists two different perspectives. These PL band can be characteristic displacement of Cu + ions (3d 10 ) 11,12) or characteristic displacement of Cu 2+ ions (3d 9 ), in which the electrons transfer from the donor V S or the interstitial atoms to the t 2 level of the Cu 2+ ions (3d 9 ) 13,15) in ZnS:Cu nanoparticles. However, in solution, the Cu + ions always tend to convert 35) to Cu 2+ and Cu, in addition, the participation of Cu + or Cu 2+ in ZnS: Cu is highly dependent on the synthesization process and the initial Cu ion source.…”
Section: Resultsmentioning
confidence: 99%
“…[7][8][9][10] Besides that, due to Cu element has many different oxidation states, so recently the nature of the green photoluminescence (PL) band still exists two different perspectives, in which they can be characteristic of Cu + ions (3d 10 ) 11,12) or Cu 2+ ions (3d 9 ) or the interstitial atoms. [13][14][15] Therefore, at present, the influence of Cu 2+ on the optical and photocatalytic properties of Cu doped ZnS [16][17][18] and the role of Cu + to p-type conductivity 19,20) in further applications of Cu doped ZnS thin films are still under consideration.…”
Section: Introductionmentioning
confidence: 99%
“…One of the best phosphor materials is ZnS mainly due to its wide band gap (3.7 eV) that make it a transparent material in the visible and infrared region, and large exciton binding energy (38 meV) . These properties enable it to be used in different optoelectronic devices such as emitter diodes, information transfer cells and solar cells, plus as display units and sensors.…”
Section: Introductionmentioning
confidence: 99%
“…However, some authors have obtained the hexagonal form for ZnS films and others have observed cubic structure. [10][11][12][13][14][15][16][17] The effects of annealing temperature were observed by many authors in different materials; for example, with varying the temperature of CdZnTe from room temperature to 400°C, the band gap is changed from 1.39 to 1.45 eV 18 and also in thin film of ZnMgO is deposited on a Si substrate annealed in the temperature range from 400 to 800°C in air. The results showed that the film introduces recrystallisation with increase in temperature.…”
Section: Introductionmentioning
confidence: 99%
“…However, some authors have obtained the hexagonal form for ZnS films and others have observed cubic structure. 10-17…”
Section: Introductionmentioning
confidence: 99%